Pharmacological improvement of cystic fibrosis transmembrane conductance regulator function rescues airway epithelial homeostasis and host defense in children with cystic fibrosis - Loske, Jennifer; Völler, Mirjam; Lukassen, Sören; Stahl, Mirjam; Thürmann, Loreen; Seegebarth, Anke; Röhmel, Jobst; Wisniewski, Sebastian; Messingschlager, Marey; Lorenz, Stephan; Klages, Sven; Eils, Roland; et al. (American journal of respiratory and critical care medicine, 2024)
Rationale: Pharmacological improvement of cystic fibrosis transmembrane conductance regulator (CFTR) function with elexacaftor/tezacaftor/ivacaftor (ETI) provides unprecedented improvements in lung function and other clinical outcomes in patients with cystic fibrosis (CF). However, ETI effects on impaired mucosal homeostasis and host defense at the molecular and cellular levels in the airways of patients with CF remain unknown. - - Objectives: To investigate effects of ETI on the transcriptome of nasal epithelial and immune cells from children with CF at the single-cell level. - - Methods: Nasal swabs from 13 children with CF and at least one F508del allele aged 6 to 11 years were collected at baseline and 3 months after initiation of ETI, subjected to single-cell RNA sequencing, and compared with swabs from 12 age-matched healthy children. - - Measurements and Main Results: Proportions of CFTR-positive cells were decreased in epithelial basal, club, and goblet cells, but not in ionocytes, from children with CF at baseline and were restored by ETI therapy to nearly healthy levels. Single-cell transcriptomics revealed an impaired IFN signaling and reduced expression of major histocompatibility complex classes I and II encoding genes in epithelial cells of children with CF at baseline, which was partially restored by ETI. In addition, ETI therapy markedly reduced the inflammatory phenotype of immune cells, particularly of neutrophils and macrophages. - - Conclusions: Pharmacological improvement of CFTR function improves innate mucosal immunity and reduces immune cell inflammatory responses in the upper airways of children with CF at the single-cell level, highlighting the potential to restore epithelial homeostasis and host defense in CF airways by early initiation of ETI therapy.
Gesehen am 03.01.2025